PUBLIC SUBSIDIES AND TAX MORALE: EVIDENCE FROM UNIVERSITY STUDENTS - Muamarah, Hanik Susilawati; Apriliasari, Vita; Safitra, Dhian Adhetiya; Santoso, Dwi Langgeng (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
The phenomenon of individuals enjoying direct tax benefits yet exhibiting low compliance intention provides the context for this research. Students at government-affiliated colleges (Perguruan Tinggi Kementerian Lain/ PTKL) are a unique group that benefits from tax-funded education, such as full tuition waivers. However, prior studies indicate that their willingness to underreport income remains high. This study investigates the determinants of tax morale among these students. Employing a quantitative approach, survey data from 1,341 students were analyzed using regression models. The findings indicate that tax awareness, fairness, and gender significantly predict tax morale. It implies that receiving direct benefits from taxpayer money can foster higher tax morale. The Directorate General of Taxes (DGT) should develop tailored tax education programs by highlighting these benefits. Practical recommendations include curricular integration and targeted outreach via campus tax centers and social media. The study’s unique contribution is its focus on students receiving direct tax-funded benefits, in contrast to prior research on self-funded students. It offers novel insights into how perceived personal benefits shape tax morale. Key limitations include the use of non-probabilistic sampling and a focus on a specific student context, limiting the generalizability of the findings.